Thymidylate kinase is critical for DNA repair via ATM‐dependent Tip60 complex formation. Issue 2 (10th September 2018) - Hu, Chun-Mei; Tsao, Ning; Wang, Yi-Ting; Chen, Yu-Ju; Chang, Zee-Fen
ABSTRACT: Cellular supply of deoxythymidine triphosphate (dTTP) is crucial for DNA replication and repair. Thymidylate kinase (TMPK) catalyzes the conversion of thymidine monophosphate to thymidine diphosphate, which is an essential step for dTTP synthesis. Despite their major cellular localization in cytosol, TMPK and ribonucleotide reductase (RNR) are detected at DNA damage sites for local dNDP formation. Because deoxyuridine diphosphate is synthesized by RNR, the simultaneous recruitment of TMPK and RNR to DNA damage sites is critical for preventing deoxyuridine triphosphate–mediated toxic repair. This study investigates the mechanism responsible for the recruitment of TMPK to DNA damage sites. Our data demonstrate the requirement of ataxia telangiectasia mutated (ATM) kinase activity for TMPK recruitment to DNA lesion sites. Moreover, we find that TMPK is able to form the complex with histone acetyltransferase Tip60 and RNR. Inhibition of ATM kinase reduces the complex formation and TMPK phosphorylation. Our analysis further shows the presence of TMPK phosphorylation at serine 88, which is an ATM kinase consensus site. A phosphorylation‐defective mutation at this site suppresses TMPK recruitment to DNA damage sites and the complex formation with Tip60. Finally, we provide evidence that this site is critical for the function of TMPK in DNA repair but not for catalytic activity. Together, these findings suggest that Tip60‐ATM signaling has a functional contribution to the recruitment of TMPK to DNA damage sites, thereby increasing local dTTP synthesis for DNA repair.—Hu, C.‐M., Tsao, N., Wang, Y.‐T., Chen, Y.‐J., Chang, Z.‐F. Thymidylate kinase is critical for DNA repair via ATM‐dependent Tip60 complex formation. FASEB J. 33, 2017–2025 (2019). www.fasebj.org